Sustainable development vs. sustainable biosphere - Rolston, Holmes, 1932-2025, author; Routledge, Earthscan, publisher (Colorado State University. Libraries, 2016)
In sustainability debates, there are two poles, complements yet opposites. Economy can be prioritized, with the environment contributory to economics at the center. This is sustainable development, an approach widely advocated by the United Nations. At the other pole, a sustainable biosphere model demands a baseline quality of environment. The economy must be worked out within such quality of life in a quality environment. This is advocated by the Ecological Society of America. People and their Earth have entwined destinies; that past truth continues in the present and will remain a pivotal concern in the new millennium. What we most ought to develop and sustain is a sense of respect for this wonderland planet.
Keywords: sustainable development; sustainable biosphere; ecology; environmental economics; ecological economics; respect for life; Earth